2017
DOI: 10.1183/13993003.01980-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual pulmonary obstruction on the long-term outcome of patients with pulmonary embolism

Abstract: The impact of residual pulmonary obstruction on the outcome of patients with pulmonary embolism is uncertain.We recruited 647 consecutive symptomatic patients with a first episode of pulmonary embolism, with or without concomitant deep venous thrombosis. They received conventional anticoagulation, were assessed for residual pulmonary obstruction through perfusion lung scanning after 6 months and then were followed up for up to 3 years. Recurrent venous thromboembolism and chronic thromboembolic pulmonary hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 35 publications
5
77
2
Order By: Relevance
“…The long-term course of PE is complicated by several adverse events including recurrent venous thromboembolism (VTE), development of chronic thromboembolic pulmonary hypertension (CTEPH), and major bleeding due to anticoagulant therapy. [1][2][3] Furthermore, methodically heterogeneous studies demonstrated that residual perfusion defects can be detected in up to 50% of the patients after 6 months using ventilation-perfusion lung scan [4][5][6] and that approximately 50% of patients suffer from persisting symptoms and cardiopulmonary functional limitations up to 1 year after the initial PE. 3,[7][8][9] While the long-term hemodynamic and functional consequences of an acute PE have received increasing attention during the past years, the burden of an acute PE on patients' psychological-emotional well-being and QoL has remained insufficiently studied thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term course of PE is complicated by several adverse events including recurrent venous thromboembolism (VTE), development of chronic thromboembolic pulmonary hypertension (CTEPH), and major bleeding due to anticoagulant therapy. [1][2][3] Furthermore, methodically heterogeneous studies demonstrated that residual perfusion defects can be detected in up to 50% of the patients after 6 months using ventilation-perfusion lung scan [4][5][6] and that approximately 50% of patients suffer from persisting symptoms and cardiopulmonary functional limitations up to 1 year after the initial PE. 3,[7][8][9] While the long-term hemodynamic and functional consequences of an acute PE have received increasing attention during the past years, the burden of an acute PE on patients' psychological-emotional well-being and QoL has remained insufficiently studied thus far.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 ). Only 3 published studies have examined the effect of persistent perfusion disorders in relation to clinical endpoints 5,9,10 . Of these, only Pesavento reported that the persistence of perfusion defects after 3 years of initial TED correlates with combined endpoint of CTEPH development + TED recurrence 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 published studies have examined the effect of persistent perfusion disorders in relation to clinical endpoints 5,9,10 . Of these, only Pesavento reported that the persistence of perfusion defects after 3 years of initial TED correlates with combined endpoint of CTEPH development + TED recurrence 5 . No remaining studies have shown any statistically significant correlation of persistent defects with higher incidence of recurrence of pulmonary embolism 9 or unfavourable patient outlook 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations